Potensi Penghematan Energi Pada Industri Farmasi - Harmen . (JURNAL MECHANICAL, 2012)
This research is focus to identify and calculated energy saving potential in pharmaceutical industry. Energy audit procedure is done by measure electrical power for each electrical industrial devices. Monthly electricity consumption for two years is investigated to know electricity pattern for this industri. Elctricity pattern can be used to measure electricity efficiency of this industry. The result show that this industry is over estimate on power supply from the grid. It’s investigated that 3.835.178,-IDR/month is loss. By using 200 kW gas/diesel cogeneration engine will be save 65.8 kW power.Keywords: energy saving, audit energy, energy efficiency, cogeneration, pharmaceutical industry